An experimental investigation of side overflow under live bed conditions - Agaçcioglu, H; Cosar, A (A A BALKEMA PUBLISHERS, 2000)
Side weirs have been used extensively in irrigation, land drainage, flood protection, and urban drainage works. Side-weir located on the fixed bed conditions have attracted considerable interest and research effort. The same thing however is not true for side-weirs located on the straight channels under the live bed conditions. The present study is aimed that the effect of the side overflow under the live bed conditions to the bed profile has been experimentally investigated. The secondary flow that is created by lateral flow causes very strong disturbance to the bottom topography in the main channel. The stagnation zone was observed along the inner bank and reverse flow occurred due to the stagnation zone. This study shows that the effect of the lateral flow to the bed profile depends on the approach velocity in the main channel, the dimensionless side-weir length and the size of the bed material.
Keywords: lateral flow; incipient motion; bed profile; and migration; Engineering; Mathematics; Water Resources